A school based cross-sectional study to assess the health problems and health status among school going children at Akhorigola, Rohtas District, Bihar - Joseph, Lisy; Umar, Mohammed; Kumari, Shweta; Kumar, Dipu; Kumari, Mamta (International Journal Of Community Medicine And Public Health, 2024)
Background: School-going children constitute one-fifth of the total population. They are the future of the nation’s successor generation; therefore, high-performing students are important investments in building the nation’s future. This study aimed to identify the health problems among school-going children. Methods: The current research was a cross-sectional study conducted in the Akhorigola block of Rohtas, targeting school-going children. A total of 650 participants were selected through a purposive sampling technique and assessed using a pre-structured format. The acquired data was analyzed using the statistical package for the social sciences (SPSS) to calculate the results based on objectives and hypotheses. Results: The outcomes of the study showed that among the 360 school-age boy participants, 210 (58.33%) had a normal weight, 100 (27.79%) were underweight, and 50 (13.88%) were overweight. Among the 290 girl participants, 150 (51.82%) had a normal weight, 110 (37.84%) were underweight, and 30 (10.34%) were overweight. The study also revealed that the majority of the 650 participants, 149 (22.92%), had inadequate personal hygiene, 109 (16.76%) had dental caries, 78 (12%) were affected by worm infestation, 55 (8.46%) were anemic, 47 (7.23%) had vitamin-A deficiency, 44 (6.76%) had scalp and hair problems, 38 (5.84%) had ear problems, and 30 (4.61%) had impaired visual acuity. Conclusions: Implementing school health programs can pose several challenges, but these can be effectively tackled through the integration of activities between the health and education departments.